Structure of a C‐terminal AHNAK peptide in a 1:2:2 complex with S100A10 and an acetylated N‐terminal peptide of annexin A2. (30th December 2012) - Ozorowski, Gabriel; Milton, Saskia; Luecke, Hartmut
<x xml:space="preserve">Abstract</x> AHNAK, a large 629 kDa protein, has been implicated in membrane repair, and the annexin A2–S100A10 heterotetramer [(p11)2(AnxA2)2)] has high affinity for several regions of its 1002‐amino‐acid C‐terminal domain. (p11)2(AnxA2)2 is often localized near the plasma membrane, and this C2‐symmetric platform is proposed to be involved in the bridging of membrane vesicles and trafficking of proteins to the plasma membrane. All three proteins co‐localize at the intracellular face of the plasma membrane in a Ca2+‐dependent manner. The binding of AHNAK to (p11)2(AnxA2)2 has been studied previously, and a minimal binding motif has been mapped to a 20‐amino‐acid peptide corresponding to residues 5654–5673 of the AHNAK C‐terminal domain. Here, the 2.5 Å resolution crystal structure of this 20‐amino‐acid peptide of AHNAK bound to the AnxA2–S100A10 heterotetramer (1:2:2 symmetry) is presented, which confirms the asymmetric arrangement first described by Rezvanpour and coworkers and explains why the binding motif has high affinity for (p11)2(AnxA2)2. Binding of AHNAK to the surface of (p11)2(AnxA2)2 is governed by several hydrophobic interactions between side chains of AHNAK and pockets on S100A10. The pockets are large enough to accommodate a variety of hydrophobic side chains, allowing the consensus sequence to be more general. Additionally, the various hydrogen bonds formed between the AHNAK peptide and (p11)2(AnxA2)2 most often involve backbone atoms of AHNAK; as a result, the side chains, particularly those that point away from S100A10/AnxA2 towards the solvent, are largely interchangeable. While the structure‐based consensus sequence allows interactions with various stretches of the AHNAK C‐terminal domain, comparison with other S100 structures reveals that the sequence has been optimized for binding to S100A10. This model adds new insight to the understanding of the specific interactions that occur in this membrane‐repair scaffold.